(untitled) (Journal of Atomic and Molecular Sciences, 2018)
The structure of a schiff base containing phenylalanine derived from curcumin has been studied by computational simulations using density functional theory (DFT) and time-dependent density functional theory (TD-DFT) at B3LYP/6-311G^** level. According to the theoretical calculations of three tautomers, enolic tautomer (A), eneamine tautomer (B) and ketonic tautomer (C), of the schiff base molecular, the geometry, relative stability, charge density population and UV-Vis characteristics of every tautomer are investigated. The calculation results demonstrate that the eneamine tautomer (B) is the most stable one and the stability of tautomers decreases in the sequence: B>A>C. The λ_max of each tautomer mainly originates from the π-π* electronic transition, involving the intramolecular charge transfer. The intramolecular proton transfer caused by electron transitions can result in the interconversion of A and B with a low energy barrier. Water can make the UV-Vis spectra of A and B exhibit remarkable red shift, increasing oscillator strength and absorption intensity. On the contrary, water can make C demonstrate a spectrum without shift, decreasing oscillator strength and absorption intensity.